1998
DOI: 10.1111/j.2042-7158.1998.tb03307.x
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Variations in the Pharmacokinetics of Pentoxifylline in Man

Abstract: Optimization of therapy by chronopharmacology requires knowledge of rhythmic manifestations of disease activity and chronopharmacokinetic data of the drugs prescribed. Rhythmic functioning of the cardiovascular system in healthy and diseased subjects is manifested as circadian rhythms in blood pressure, cardiac output, heart rate, etc. The disposition of several cardiovascular drugs in man has been reported to be time-dependent. This study reports the effect of time of administration on the disposition of pent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…31 In contrast, PTX is cleared off very fast. 32 Therefore, suramin administration followed by PTX is more appropriate as it gives a window where both the drugs are present and can interact. Suramin and PTX treatment for 24 hr showed concentration-dependent inhibition in F10 cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…31 In contrast, PTX is cleared off very fast. 32 Therefore, suramin administration followed by PTX is more appropriate as it gives a window where both the drugs are present and can interact. Suramin and PTX treatment for 24 hr showed concentration-dependent inhibition in F10 cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…From the above paragraphs it is evident that the time dependent pharmacokinetics of some drugs (nifedipine and isosorbide-5-mononitrate) are masked upon administering them as sustained release dosage froms, whereas in other cases (indometacin, verapamil) even sustained release dosage forms also exhibited chronokinetics. Earlier we have reported (Srinivasu et al 1998) that pentoxifylline given as immediate release capsule exhibited dosing time related changes in its pharmacokinetics resulting in significantly lowered C max and increased T max , Vss/f, T 1/2 and MRT following 01:00 h administration when compared with 07:00, 13:00 and 19:00 h dosing. In the present study similar changes in C max and Vss/f are observed.…”
Section: Discussionmentioning
confidence: 86%
“…Pentoxifylline (CAS-6493-05-6) owing to its short half-life is generally administered in the form of sustained release tablets for prophylactic as well as therapeutic uses. The chronopharmacokinetics of pentoxifylline following its administration as immediate release capsules was reported earlier (Srinivasu et al 1998). In this study we have investigated the influence of circadian rhythms on the pharmacokinetics of sustained release tablets of pentoxifylline in healthy subjects.…”
Section: Introductionmentioning
confidence: 83%
“…As urinary elimination was unaffected by dosing time, these variations were attributed to oscillations of hepatic clearance, which encompasses metabolic and biliary clearance (Canal et al, 1991). Identically, Srinivasu, Rao, Rao, and Rambhau (1998) partly attributed the lower C max of pentoxifylline at 01.00 hr to its biliary excretion and extensive enterohepatic circulation (Table 3).…”
Section: Chronopharmacokinetics: Human Datamentioning
confidence: 96%